Chemopreventive effects of pomegranate fruit extract on acrylamide induced lung, liver and testis carcinogenesis in male laka mice - Jayanand Manjhi; Anvesha Sinha; Renuka Ganger; Durg V. Rai; Vinod K. Gupta (International Journal of Phytomedicine, 2014)
Objective: The present study was aimed to test the efficacy of pomegranate fruit extract to induce apoptosis in the artificially induced tumor cells in mice. Method: Adult male LAKA-UK mice (30-40g) were divided into four groups, viz. control, AA, PFE and PFE+AA. Induction of carcinogenesis by intra -peritoneal administration of acrylamide was preceded by PFE treatment in PFE+AA group. At the end of study animals were sacrificed by decapitation under deep anesthesia and organs (lung, liver and testes) were resected to evaluate activities of various enzymes such as CAT, SOD, GPx, GSH and GST in different experimental groups. MTT assay and histological examination of lung and liver sections were also conducted. Result: Administration of acrylamide resulted in the increase SOD, GPx and GSH activities, which decreased significantly (p<0.05) in PFE+AA group. The MTT assay showed high cell proliferation in the AA group of mice which lessened in treatment groups. Similarly the histological examinations exhibited alveolar wall destruction and air space enlargement in pulmonary tissues and larger vacuolization in the hepatic tissues due to acrylamide administration, whereas in PFE+AA cells it was found to be normal. Conclusion: Pomegranate fruit extract was observed to be a potential treatment intervention that not only prevents the onset and progress of carcinogenesis but also helps in the initiation of apoptosis and refurbishment of the damaged cellular architecture.